THE CRYSTAL STRUCTURE OF FENAKSITE K2NA2FE2SI8O20 - Rozhdestvenskaya I.V.; Bannova I.I.; Nikishova L.V.; Soboleva T.V. (My University, 2004)
Fenaksite K2Na2Fe2Si8O20 was discovered by M.D. Dorfman in Khibiny in 1959. Its crystal structure was determined and refined with the application of photomethod up to R = 0.148. We studied the stucture of synthetic fenaksite based on XRD data. The results obtained made it possible to refine the structure of this mineral and compare it with the topologically similar structures of agrellites.